Kola Sami in the Stalinist Terror: A Quantitative Analysis - Kotljarchuk, Andrej (Journal of Northern Studies, 2013)
The study is focused on aspects that have been understudied by previous research on the Kola Sami. First there is a quantitative analysis of the Sami victims of the Stalinist terror. Second there is a discussion of the short- and long-term roles of state violence for the affected indigenous community. Most prior studies of the ethnic aspects of the Stalinist terror have focused on the large Diaspora nationalities or post-war deportations, while this paper concentrates on a small homogenous indigenous community. The study reaches a new level of accuracy about the nature of Soviet terror, and who became victims and why.